Effects of Organic Pollutants on Bacterial Communities Under Future Climate Change Scenarios - Rodríguez, Juanjo; Gallampois, Christine M. J.; Timonen, Sari; Andersson, Agneta; Sinkko, Hanna; Haglund, Peter; Berglund, Åsa M. M.; Ripszam, Matyas; Figueroa, Daniela; Tysklind, Mats; Rowe, Owen (Frontiers in Microbiology, 2018)
Coastal ecosystems are highly dynamic and can be strongly influenced by climate change, anthropogenic activities (e.g. pollution) and a combination of the two pressures. As a result of climate change, the northern hemisphere is predicted to undergo an increased precipitation regime, leading in turn to higher terrestrial runoff and increased river inflow. This increased runoff will transfer terrestrial dissolved organic matter (tDOM) and anthropogenic contaminants to coastal waters. Such changes can directly influence the resident biology, particularly at the base of the food web, and can influence the partitioning of contaminants and thus their potential impact on the food web. Bacteria have been shown to respond to high tDOM concentration and organic pollutants loads, and could represent the entry of some pollutants into coastal food webs. We carried out a mesocosm experiment to determine the effects of: 1) increased tDOM concentration, 2) organic pollutant exposure, and 3) the combined effect of these two factors, on pelagic bacterial communities. This study showed significant responses in bacterial community composition under the three environmental perturbations tested. The addition of tDOM increased bacterial activity and diversity, while the addition of organic pollutants led to an overall reduction of these parameters, particularly under concurrent elevated tDOM concentration. Furthermore, we identified 33 bacterial taxa contributing to the significant differences observed in community composition, as well as 35 bacterial taxa which responded differently to extended exposure to organic pollutants. These findings point to the potential impact of organic pollutants under future climate change conditions on the basal coastal ecosystem, as well as to the potential utility of natural bacterial communities as efficient indicators of environmental disturbance.